Review: Colchicine, current advances and future prospects - RAVINDRA ADE; MAHENDRA KUMAR RAI (Smujo International, 2010)
Abstract. Ade R, Rai MK. 2010. Colchicine, current advances, and future prospects. Nusantara Bioscience 2: 90-96. Colchicine is a toxic natural compound and secondary metabolite commonly produced by plants like Colchicum autumnale and Gloriosa superba. It is originally used to treat rheumatic complaints, especially gout, and still finds its uses for these purposes today despite dosing issues concerning its toxicity. It is also prescribed for its cathartic and emetic effects. Initially, oral colchicine has not been approved as a drug by U.S. Food and Drug Administration (FDA). But now FDA approved colchicine as a drug for some disorders. Colchicine's present medicinal use is in the treatment of gout and familial Mediterranean fever. It is also being investigated for its use as an anticancer drug. In neurons, axoplasmic transport is disrupted by colchicine. Due to all the pharmacological application of colchicine, there is an urgent need to enhance the properties and increase the production of colchicine with the help of in vitro technologies. The present review is mainly focused on the chemistry of colchicine, its medicinal uses, and toxicity.